Research on the measurement and characteristics of museum visitors’ emotions under digital technology environment - Zhang, Ting; Qi, Zipeng; Guan, Weiwei; Zhang, Cheng; Jin, Dingli (Frontiers in Human Neuroscience, 2023)
Abstract：What kind of emotional experience does the application of digital technology in museums create for museum visitors? Can it be measured accurately and in real-time? What are its characteristics? This paper aims to explore the immediate and accurate measurement of the emotional experiences of museum visitors from a psychological perspective. By using the Ningbo Tianyi Pavilion Museum visitors as the research sample, the study utilizes EEG signals and the PAD emotion model to comprehensively measure the digital emotional experiences of museum visitors based on their physiological and psychological reactions. The results show that: (1) In a quasi-experimental environment, linear SVM, polynomial kernel SVM, and Gaussian kernel SVM can all accurately classify the emotional tendencies of museum visitors with success rate of over 72%. (2) In a quasi-experimental environment, it is feasible and reliable to measure the immediate digital emotional experiences of visitors using EEG signals and the PAD emotion model. Based on this, we can summarize the characteristics of emotional tendencies among different demographic groups of museum visitors.